On the Irreducibility of Some Composite Polynomials - M. Alizadeh (Journal of Mathematical Extension, 2012)
. In this paper we study the irreducibility of some composite polynomials, constructed by a polynomial composition method over finite fields. Finally, a recurrent method for constructing families of irreducible polynomials of higher degree from given irreducible polynomials over finite fields is given